The effect of fermentation of sludge with Neorospora sp on the egg performances and quality of laying hens - Yosi Fenita; Urip Santoso; Hardi Prakoso (Jurnal Ilmu Ternak dan Veteriner, 2010)
The purpose of this research is to produce enriched eggs (high concentration in protein, amino acid and β-karoten) but law in lipid and cholesterol content. An experiment was conducted to study the utilization of fermented palm oil sludge (LSF) using neurospora sp for layer. The present study was done based on Randomized Design in which 100 layer were distributed to five treatment group as follow: Layers were fed diet with (0, 5, 10, 15 and 20% LSF). Experimental results showed that LSF significantly (P < 0.05) affected egg mass production, feed comsumption, feed conversion, and HU and highly affected (P < 0.01) yolk colour. The best treatment was with 10% LSF. LSF had no effect on egg weight, shell thickness, albumen index and yolk index (P > 0.05). LSF reduced egg smell, improved taste of egg and yolk colur (P < 0.05). Protein and fat, contents of eggs were significantly reduced (P < 0.05) and cholesterol content of eggs was significantly reduced (P < 0.01). Utilization LSF increased the content of β-karoten yolk (P < 0.01), and modified the composition of amino acid in yolk. In conclusion, utilization of LSF improved egg quality, reduced egg cholesterol dan lipid and modified the composition of amino acid in yolk. Key Words: Palm Oil Sludge, Neorospora sp, Egg Quality